EARTHQUAKE OF 27 AUGUST 2008 IN THE SOUTHERN BAIKAL AREA AND ITS PRECURSORS - Rudolf M. Semenov (Геодинамика и тектонофизика, 2015)
On 27 August 2008, a strong earthquake occurred in the Southern Baikal area. Its focus was located within the Baikal rift zone which characterized with high seismicity. The general location and approximate strength of the earthquake were thus expectable, whereas the shock occurred at an unexpected time, as usual. The article provides a brief review of the geological environment and macro-seismic effects of the earthquake. It also reviews a set of seismic and hydrogeochemical indicators which are interpreted as precursors of the given earthquake. Considering such precursors, the fact that the Baikal deepwater helium content had changed before the main shock was recorded for the first time in the region under study.